APPLICATION OF THE CONCEPT OF TRANSFORMATION GEOMETRY TO THE DESIGN OF THE BPKP EMPLOYEE AWARD CHARTER FOR ACEH REPRESENTATIVE - Syarifah Meurah Yuni; Maysarah, Siti; Irawati, Cut; Nurmaulidar; Zuhra, Rahma (CV. Naskah Aceh, 2023)
Design or planning is a process of planning and making a new object that is carried out by considering various aspects including beauty, symmetry, and aesthetics as well as various other aspects. The design process can also be referred to as visual problem solving which includes organizing, creating, and evaluating to produce a desired work. An award certificate is a media that contains writing in the form of an official statement and is used as a form of appreciation for someone's achievements or accomplishments. The award certificate is created through a design planning process first, where all ideas are conveyed through the creation of objects in the design. In designing the design of the certificate, the concept of transformation geometry can be applied to obtain changes in position and presentation based on several types of transformations, so that later a design will be produced that is in accordance with needs and desires. The types of transformation geometry used include translation, rotation, reflection, and dilation. This concept of transformation geometry is utilized in designing and determining the design of the charter to be given to BPKP Aceh Representative employees who have achieved.